2009
DOI: 10.1111/j.1464-5491.2009.02780.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes in women with gestational diabetes treated with metformin or insulin: a case–control study

Abstract: Women with GDM treated with metformin and with similar baseline risk factors for adverse pregnancy outcomes had less weight gain and improved neonatal outcomes compared with those treated with insulin. Diabet. Med. 26, 798-802 (2009).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
95
7
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 18 publications
15
95
7
6
Order By: Relevance
“…Metformin treatment has been shown to be associated with reduced rates of PE, when used from early gestation in women with polycystic ovarian syndrome [31]. However, this finding is not universal and other studies in PCOS, type 2 diabetes mellitus and GDM have not reported the same association [32][33][34]. The MiG trial, from which these data are taken, did not find any difference in rates of PE in women allocated to metformin compared with those allocated to insulin for treatment of GDM, and the two groups did not differ in glycemic control attained [12].…”
Section: Discussioncontrasting
confidence: 47%
“…Metformin treatment has been shown to be associated with reduced rates of PE, when used from early gestation in women with polycystic ovarian syndrome [31]. However, this finding is not universal and other studies in PCOS, type 2 diabetes mellitus and GDM have not reported the same association [32][33][34]. The MiG trial, from which these data are taken, did not find any difference in rates of PE in women allocated to metformin compared with those allocated to insulin for treatment of GDM, and the two groups did not differ in glycemic control attained [12].…”
Section: Discussioncontrasting
confidence: 47%
“…The pregnancy outcomes in the women who were treated with metformin alone, demonstrated lesser incidence of prematurity, neonatal jaundice and admission to neonatal unit with an overall improvement in neonatal morbidity as compared to the women treated with insulin alone. There was no significant difference in the incidence of fetal macrosomia between the two groups of women [29].…”
Section: Ii) Metformin In Gestational Diabetesmentioning
confidence: 71%
“…In the light of the MiG findings, we conducted a case-control observational study comparing pregnancy outcomes in 100 women with GDM exclusively treated with metformin vs 100 with GDM exclusively treated with insulin and matched for age, weight, and ethnicity [29]. Both groups had similar baseline maternal risk factors.…”
Section: Ii) Metformin In Gestational Diabetesmentioning
confidence: 99%
“…Neste estudo, metade das gestantes aplicou 1000 mg diárias de metformina isoladamente e o outro grupo aplicou a terapia com insulina correspondente à idade, peso e etnia. Os resultados estatísticos novamente apontaram uma redução significativa no ganho de peso das gestantes que administraram metformina (p <0,001) (BALANI et al, 2009).…”
Section: Resultados Nas Terapias Metformina Versusunclassified